Panchakosha: Foundations for Holistic Child Development - Chapagain, Purushottam (Journal of Training and Development, 2025)
The Panchakosha theory, a cornerstone of ancient wisdom, offers a comprehensive framework for understanding the multifaceted nature of human beings emphasizing the nurturing of all five layers of being. This theory’s application in education can revolutionize the way we approach child development, integrating the physical, emotional, intellectual, and spiritual dimensions. By incorporating elements such as Yoga Nidra, meditation, yoga philosophy, and mindful nutrition, educators can foster holistic growth in children and instill valuable social and personal disciplines promoting better concentration, calmness, and improved learning and memory. Educational philosophies from both Eastern and Western traditions, including contributions from notable thinkers, shape diverse and effective teaching methods. This article delves into the practical ways in which the Panchakosha Theory can be applied to education, offering insights into yogic practices, storytelling, and pedagogical strategies that align with both Eastern and Western educational philosophies.